Usefulness of cytology and visual inspection with acetic acid in the detection of neoplastic lesions of the cervix at the Centro Médico Oncomujer during 2013-2014. Lima, Peru - Rosado Flores, Manuel Jesús (2017)
Objective: To determine the usefulness of cytology and visual inspection with acetic acid in the detection of neoplastic lesions of the cervix. Materials and methods: An observational, retrospective, descriptive and cross-sectional study. A population of female patients who attended the Centro Médico Oncomujer between 2013 and 2014 for a cervical cancer screening with Pap test and VIA was evaluated. Women referred for biopsy and with a positive result in one or both tests (Pap-VIA) were included in the study. Results: The mean age was 41.66 years old (range: 20-50 years). One thousand one hundred eight (1108) patients were evaluated with Pap smear and VIA: 8.2% (92/1108) of the patients evaluated by Pap smear had a positive result and 27.6% (306/1108) of those evaluated by VIA tested positive. The results of the cytology (Pap smear) against the biopsy showed a sensitivity of 30.6% (95% CI: 23.7%-3.48%), specificity of 88.4% (95% CI: 77.89.7%-94.51%), positive predictive value of 85.9% (95% CI: 73.65%-999.48%) and negative predictive value of 35.4% (95% CI: 28.43%-43.16%). The results of VIA against the biopsy showed a sensitivity of 99.3% (95% CI: 96.04%-99.97%), specificity of 5.8% (95% CI: 1.87%-14.93%), positive predictive value of 70.9% (95% CI: 64.49%-76.74%) and negative predictive value of 80% (95% CI: 29.88%-98.953.16%). Conclusions: The high false-positive rate of VIA can lead to overtreatment, regardless of the advantages of its use, especially in remote and low-income populations.